Application of Data-Driven Method for HVAC System (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint, entitled “Application of data-driven method for HVAC System”, is dedicated to providing an overview of the latest achievements in the application of data-driven methods for HVAC systems. Topics of interest include, but are not limited to, the following: fault detection and diagnosis of HVAC systems; energy consumption prediction; model predictive control; data mining and analysis of HVAC systems; data mining and analysis of building environment; energy conservation; energy saving.